Ecological responses of two shrimp populations (Palaemonidae) to seasonal abiotic factor variations in a Brazilian semiarid reservoir. Issue 5 (2nd September 2020) - De Lucena, Isis C.; Do Nascimento, Whandenson M.; Pinheiro, Allysson P.; Cascon, Paulo
Abstract : The objective of this study was to evaluate if seasonal abiotic factor variations (pluviosity, depth, temperature, dissolved oxygen, hydrogen potential, ammonia and electrical conductivity) in a northeastern semiarid reservoir influence abundance and population structure variations in Palaemonidae Macrobrachium amazonicum and M. jelskii shrimp. Data were collected bimonthly from 30 reservoir sampling sites from October 2016 to September 2017 during the dry and rainy seasons. A principal component analysis determined the abiotic factors that explained most of the data variations, then a multivariate permutational variance analysis showed significant differences in abiotic variables between the dry and rainy periods. The shrimp were more abundant during the dry season compared to the rainy season, and the M. amazonicum species was more abundant than the M. jelskii species across both periods. Additionally, redundancy analysis for each seasonal period indicated that seasonal abiotic factor variations caused different responses in the abundance of intrapopulation groups (females, males and juveniles) in the two studied shrimp species. The present results suggest that related shrimp species may present different responses to seasonal abiotic factor variations, suggesting these ecological differences may be crucial to ensure a stable coexistence. Moreover, high plasticity appears to provide M. amazonicum and M. jelskii a good adaptation, especially to life in reservoirs, which are unstable environments.